Cognitive impairment combined with depression PTSD signs in civilians affected by the Russian Federation aggression - Долинський, Роман (Psychosomatic Medicine and General Practice, 2024)
Cognitive disorders and depression, joined with post-traumatic stress disorders, substantially deteriorate patient condition and social adaptation. This study involved 129 civilians (117 women and 12 men) aged 18-60, frontline area residents of Chernihiv, Kharkiv, Dnipro and Sumy oblast. A total of 119 (92.2% patients) had depression signs, and in 64 (49.6%) cognitive impairment was detected. The cognitive impairment was significantly dependent on the depression scale in patients with moderate PTSD (OD 5.06 and RD 30.32). In this group, in patients with the maximum depression severity (20-27 score in PHQ-9), OD and RD of cognitive impairment were 63.33. Importantly, in the case of mild and severe PTSD, depression severity and its impact on cognitive impairment were not that expressed, with OD of 3.0 and RD of 25.0, OD of 1.14, and RD of 5.0, respectively. Thus, patients with mild and moderate PTSD and depression are a priority group for medication and psychotherapy to prevent the progression of cognitive impairment.